2012
DOI: 10.1021/jz201583n
|View full text |Cite
|
Sign up to set email alerts
|

Protonated Carboxyl Anchor for Stable Adsorption of Ru N749 Dye (Black Dye) on a TiO2 Anatase (101) Surface

Abstract: We have investigated the adsorption stability of ruthenium N749 dye [black dye (BD)], a highly efficient dye for dye-sensitized solar cells (DSCs), through protonated and deprotonated carboxyl group anchors on a TiO2 anatase (101) surface by using first-principles calculations. Geometry optimizations of the surface system with a supercell and the UV-visible spectrum calculation of the optimized dye structure were carried out. Among the configurations with one and two anchors, the BD adsorption anchored with on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 35 publications
8
52
1
Order By: Relevance
“…4c) with the TiO 2 surface, 198 depending on the structure of the dye, the binding groups, the pH, and the metal oxide synthesis. In this regard, polypyridine complexes of d 6 metal, such as Ru(II), 79,81,84 Os(II) 79,84 or Ru(I), 91 are typical examples of compounds characterized by intense bands in the visible region due to MLCT transition. In this regard, polypyridine complexes of d 6 metal, such as Ru(II), 79,81,84 Os(II) 79,84 or Ru(I), 91 are typical examples of compounds characterized by intense bands in the visible region due to MLCT transition.…”
Section: Metal Complexesmentioning
confidence: 99%
“…4c) with the TiO 2 surface, 198 depending on the structure of the dye, the binding groups, the pH, and the metal oxide synthesis. In this regard, polypyridine complexes of d 6 metal, such as Ru(II), 79,81,84 Os(II) 79,84 or Ru(I), 91 are typical examples of compounds characterized by intense bands in the visible region due to MLCT transition. In this regard, polypyridine complexes of d 6 metal, such as Ru(II), 79,81,84 Os(II) 79,84 or Ru(I), 91 are typical examples of compounds characterized by intense bands in the visible region due to MLCT transition.…”
Section: Metal Complexesmentioning
confidence: 99%
“…We have established that the species BD_2Hll and the BD_1Hc are the most stable diproton-Ve ry recently, the adsorption mode of the BD on TiO 2 has also been computationally investigated using both cluster and periodic boundary conditions approaches. [34][35][36] The optical absorption spectrum of the BD adsorbed onto TiO 2 clusters (BD@TiO 2 ) has also been calculated, [35] although a simplified TiO 2 model was employed which did not allow full exploration of the possible dye binding modes. [36] The work by Sodeyama et al on the other hand, explored in detail the possible dye binding modes on TiO 2 in vacuo, but reported simulated optical properties for the isolated dye at their adsorption geometry.…”
Section: Molecular Structure Of the Isolated Bdmentioning
confidence: 99%
“…[17] Due to the great experimental interest and the high efficiency of the BD, various theoretical studies on this system have been reported. [27][28][29][30][31][32][33][34][35][36] In particular, a few computational works have been focused on the electronic structure of the BD [28] and on the optical properties of the monoprotonated [29] and on the fully protonated, di-and mono-protonated and fully deprotonated forms of BD. [31] Also a study on the electronic structure and absorption spectra of linkage isomers of BD has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] However, it is unclear whether the behavior of dye molecules on a single crystal surface is faithfully reproduced by molecules on nanocrystalline TiO 2 , which is the material used for photovoltaic cell electrodes. Direct observations are very difficult because of the complex structure of nanocrystalline TiO 2 , so a high-resolution method with high specificity is required for observing the microscopic structure of the surface morphology of these porous materials.…”
Section: Introductionmentioning
confidence: 99%